The Influence of Principals’ Transformational Leadership, the Work Environment, and Organizational Commitment on the Performance of Teachers at Public Junior High Schools in North Banjarmasin Subdistrict - Tri Ananda Setiyani; Novitawati Novitawati; Noorhapizah Noorhapizah (FKIP - Universitas Riau, 2026)
This study examined the direct and indirect effects of the principal’s transformational leadership and the work environment on teacher performance through organizational commitment among public junior high school teachers in North Banjarmasin District. A quantitative survey design with path analysis was employed. The population comprised 236 teachers, and 148 respondents were selected using proportional random sampling. Data were collected through valid and reliable Likert-scale questionnaires and analyzed using descriptive statistics, multiple linear regression, path analysis, and the Sobel test. The findings revealed that transformational leadership had a positive and significant effect on organizational commitment and teacher performance. The work environment significantly influenced organizational commitment but had no direct significant effect on teacher performance. Organizational commitment positively affected teacher performance and mediated the relationships between transformational leadership, the work environment, and teacher performance. These findings suggest that strengthening transformational leadership, creating a supportive work environment, and enhancing organizational commitment are essential strategies for improving teacher performance and overall school effectiveness.